A retrospective cohort study of mode of delivery among public and private patients in an integrated maternity hospital setting. Issue 11 (25th November 2013) - Murphy, Deirdre J; Fahey, Tom
Abstract : Objective: To examine the associations between mode of delivery and public versus privately funded obstetric care within the same hospital setting. Design: Retrospective cohort study. Setting: Urban maternity hospital in Ireland. Population: A total of 30 053 women with singleton pregnancies who delivered between 2008 and 2011. Methods: The study population was divided into those who booked for obstetric care within the public (n=24 574) or private clinics (n=5479). Logistic regression analyses were performed to examine the associations between operative delivery and type of care, adjusting for potential confounding factors. Main outcome measures: Caesarean section (scheduled or emergency), operative vaginal delivery (vacuum or forceps), indication for caesarean section as classified by the operator. Results: Compared with public patients, private patients were more likely to be delivered by caesarean section (34.4% vs 22.5%, OR 1.81; 95% CI 1.70 to 1.93) or operative vaginal delivery (20.1% vs 16.5%, OR 1.28; 95% CI 1.19 to 1.38). The greatest disparity was for scheduled caesarean sections; differences persisted for nulliparous and parous women after controlling for medical and social differences between the groups (nulliparous 11.9% vs 4.6%, adjusted (adj) OR 1.82; 95% CI 1.49 to 2.24 and parous 26% vs 12.2%, adj OR 2.08; 95% CI 1.86 to 2.32). Scheduled repeat caesarean section accounted for most of the disparity among parous patients. Maternal request per se was an uncommonly reported indication for caesarean section (35 in each group, p<0.000). Conclusions: Privately funded obstetric care is associated with higher rates of operative deliveries that are not fully accounted for by medical or obstetric risk differences.